Balancing the Opposing Principles That Govern Peroxisome Homeostasis. Issue 3 (March 2021) - Mahalingam, Shanmuga S.; Shukla, Nandini; Farré, Jean-Claude; Zientara-Rytter, Katarzyna; Subramani, Suresh
Abstract : Despite major advances in our understanding of players and mechanisms involved in peroxisome biogenesis and peroxisome degradation, very few studies have focused on unraveling the multi-layered connections between, and the coordination of, these two opposing processes that regulate peroxisome homeostasis. The intersection between these processes also provides exciting avenues for future research. This review highlights the links between peroxisome biogenesis and degradation, incorporating an integrative approach that is critical not only for a mechanistic understanding, but also for manipulating the balance between these processes in relevant disease models. Highlights: Emerging studies on the integration and coordination of the opposing processes of peroxisome biogenesis and pexophagy present new vistas for research. Physiologically, the processes of organelle biogenesis and turnover must be interconnected and regulated. For example, some peroxisomal metabolites could act as crucial signaling cues to inhibit biogenesis and trigger pexophagy to achieve a coordinated response to a changing cellular state. Moreover, signals that induce peroxisome biogenesis must keep pexophagy in check and vice versa. Multiple common molecular platforms, representing nodes for regulation, are used to balance peroxisome biogenesis and pexophagy. Because peroxisomes are essential in humans and there are disease states associated with peroxisomes and their functions, an understanding of the two arms of homeostasis may help in therapeutic interventions. Studies of peroxisome homeostasis will also shed light on principles involved in the homeostasis of other organelles.